Adolescent Psychological Disorders Linked to Premenstrual Syndrome (PMS): Gangguan Psikologis Remaja yang Berhubungan dengan Sindrom Premenstruasi (PMS) - Sari, Mayang; Azizah, Nurul (Inquest Journal, 2023)
Premenstrual syndrome (PMS) occurs during the luteal phase, causing symptoms like physical discomfort, emotional instability, and behavioral changes that disrupt daily activities, particularly affecting adolescents' psychological well-being. This case study examines Ms. K's psychological condition during PMS, highlighting her unstable mood and irritability. Addressing her psychological symptoms involved activities to improve her mood and consuming chocolate, which contains antioxidants with potential medical and psychological benefits. The study aims to explore the effectiveness of these interventions. Findings suggest that mood-enhancing activities and chocolate consumption can alleviate psychological distress during PMS, offering practical implications for managing PMS-related psychological disorders.